Pengaruh Aktivitas Pertambangan Nikel terhadap Daya Serap Tenaga Kerja dan Tingkat Kesejahteraan Masyarakat - Irwansyah Aljauhar; Mimi Arifin; Isfa Sastrawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
Mining is a capital-intensive industry. The mining industry has made an important contribution in the development of disadvantaged areas to become new growth centers in line with the opening of mining in the area. Kabaena Island is one of the regions in Bombana Regency which has a large enough mining sector potential, especially nickel. Despite having a large nickel potential, the island is still classified as a disadvantaged area with a low level of welfare. The purpose of this study is to determine the effect of the presence of nickel mining on employment of local people and its effect on improving the welfare of the community, especially those working for nickel mining companies. This study uses descriptive statistical methods, with multiple linear regression analysis techniques, comparative, comparative levels of labor welfare, and crosstab. The results of this study indicate that the presence of a nickel mining company on the island of Kabaena is able to create new jobs and absorb labor, especially local community workforce. In addition, the presence of nickel mining companies has a positive impact on the welfare of local communities, especially those working in nickel mining companies.